Study of Construction Project Delay Due to COVID-19 Pandemic in Construction Industry - Lam, Jing Yin; ZAINAL, ROZLIN; KASIM, NARIMAH; SHAREH MUSA, SHARIFAH MERYAM (Research in Management of Technology and Business, 2022)
The pandemic of COVID-19 had arisen into our global that had affected the construction industry. Due to the COVID-19 pandemic, most construction project delays have occurred. The purpose of this research is to identify the impacts of the COVID-19 pandemic on construction project delay and the strategies to cope with the COVID-19 pandemic. The majority of contractors in Sibu Town, Sarawak registered in Grade 1. This research uses a quantitative method to achieve all of the objectives. This study surveys the 175 perceptions of Grade 1 contractors in Sibu Town, Sarawak. The respondents were given a questionnaire in a link of google form through WhatsApp. A total of 108 respondents have given feedback in the questionnaire which is 61.71%. Descriptive statistic by SPSS software was used to analyse the data for all objectives. This research find that the main impact and strategy respectively delay in material delivery and two-meter social distancing rule recorded as the highest frequency. This research can be a reference to the Grade 1 contractors and the person who participated in the construction industry is aware of the most significant impact of the COVID-19 pandemic and use the most appropriate strategy to address the COVID-19 pandemic.